Heavy Metal Accumulation and Ecological Risk on Seagrass Cymodocea and Thalassia in Pahawang Island, Indonesia - Gusri, Ariqoh Athallah; Rozirwan, Rozirwan; Putri, Wike Ayu Eka; Melki, Melki; Isnaini, Isnaini; Nugroho, Redho Yoga; Mohamed, Che Abd Rahim (Marine Science Department Diponegoro University, 2025)
Seagrass species thrive in coastal ecosystems and known for their ability to accumulate heavy metals from their surrounding environment. This study aims to evaluate the ecological risks related to the accumulation of heavy metals in seagrass roots, leaves, and sediments. The seagrass examined belong to the genera Cymodocea and Thalassia, collected from two sites: Jeralangan and Cukuh Nyai on Pahawang Island, Lampung, Indonesia. The heavy metals analyzed included Pb, Cu, Ni, and Zn, which were measured using the wet destruction method and quantified with a SHIMADZU AA-7000 Atomic Absorption Spectrophotometer (AAS). The ecological risk was evaluated through various indices, such as the Bioconcentration Factor (BCF), Translocation Factor (TF), Geoaccumulation Index (Igeo), Contamination Factor (Cf), and Pollution Load Index (PLI). The highest concentrations of heavy metals in sediment were detected at station 1 was Zn (15.486 mg.kg-1). In the roots of Cymodocea was Zn (8.772 mg.kg-1), while the highest concentration in leaves was Cu in Thalassia (10.541 mg.kg-1). The ecological risk assessment revealed that BCF < 1 categorize an excluder, while TF > 1 for Pb and Zn indicate effective translocation from roots to leaves. Additionally, Igeo < 0 signify no contamination, Cf < 1 indicate low pollution levels, and PLI < 0 confirm a non-polluted status. In conclusion, the results show that the seagrass ecosystems at the study sites currently have low levels of heavy metal pollution and minimal ecological risk, suggesting they remain in a relatively safe condition.